The Effect of Green Advertising on Environmental Attitudes and Purchase Intention in Buying Environmentally Friendly Products (Studies on Garnier Products) - Nabahani, Putri Rakhmatia; Asih, Daru; Malihah, Fadhila Dhia; Fajrin, Nurul Komara (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives This study aims to determine green advertising on purchase intention in buying environmentally friendly products through mediating environmental attitudesMethodology: This research employed a causality research design, utilizing a quantitative approach. Data were collected through a questionnaire distributed via Google Forms to residents of DKI Jakarta. Sampling was conducted using the Non-Probability Sampling technique, specifically employing a purposive sampling method. The sample size for this study was 100 participants. Subsequently, the questionnaire responses were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, facilitated by SmartPLS 3.0 software.Finding: The results of this study found that Garnier’s green advertising and environmental attitudes had a positive and significant effect on purchase intentions in buying Garnier’s environmentally friendly product, and environmental attitudes had a positive and significant effect in mediating green advertising towards purchase intention in buying environmentally friendly product.Conclusion: The better implementation of green advertising increases consumer interest in buying environmentally friendly products, the higher the consumer's environmental attitude, and the greater the individual's interest in buying environmentally friendly products.